The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1088/1755-1315/733/1/012090
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals properties of avocado seed: A review

Abstract: Persea americana Mill. seed or avocado seed contains phytochemical components such as flavonoids, tannins, saponins, phenolic, and alkaloid. The phenolic compounds of avocado seed are mainly catechin, hydroxybenzoic acid, caffeic acid, chlorogenic acid, coumaric acid, ferulic acid, and triterpenoid glycosides. This review also discusses various extraction methods using an organic solvent, inorganic solvent, and a mixture of solvents. The analysis methods to measure the chemical properties of extracted phytoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 12 publications
0
23
0
1
Order By: Relevance
“…PS(+)MS full scan of ethanol extract from peel of avocado can be found in Supplementary Materials, Figure S1 . It is reported that, as the avocado fruit develops, the carbohydrate amount decreases and the fatty acids and secondary metabolites content increases [ 46 , 47 ]. In ripe avocado fruits, the alkaloids constitute a remarkable percentage of the natural compounds present in the pulp [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PS(+)MS full scan of ethanol extract from peel of avocado can be found in Supplementary Materials, Figure S1 . It is reported that, as the avocado fruit develops, the carbohydrate amount decreases and the fatty acids and secondary metabolites content increases [ 46 , 47 ]. In ripe avocado fruits, the alkaloids constitute a remarkable percentage of the natural compounds present in the pulp [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that, as the avocado fruit develops, the carbohydrate amount decreases and the fatty acids and secondary metabolites content increases [ 46 , 47 ]. In ripe avocado fruits, the alkaloids constitute a remarkable percentage of the natural compounds present in the pulp [ 46 , 47 ]. From the alkaloids identified, anibine ( 1 ), duckeine ( 2 ), and anicanine ( 8 ) were not detected in PEL-ET.…”
Section: Resultsmentioning
confidence: 99%
“…Other seeds like those from avocado contain phytochemicals like flavonoids, alkaloids, saponins, tannins, etc. (Setyawan et al, 2021), which have antioxidant and antiinflammatory properties. Phenols in avocado seeds mainly include catechins, ferulic acid, coumaric acid, chlorogenic acid, caffeic acid, hydroxybenzoic acid, etc., with therapeutic and medicinal benefits (Setyawan et al, 2021).…”
Section: Seedsmentioning
confidence: 99%
“…(Setyawan et al, 2021), which have antioxidant and antiinflammatory properties. Phenols in avocado seeds mainly include catechins, ferulic acid, coumaric acid, chlorogenic acid, caffeic acid, hydroxybenzoic acid, etc., with therapeutic and medicinal benefits (Setyawan et al, 2021). Black seeds (Nigella sativa seeds) are also among excellent source of nutraceuticals (Kalonji, 2021), given the presence of trans-anethole, palmitic acid, oleic acid, linoleic acid, nigellidine, nigellicine, nigellimine N-oxide, nigellimine, etc (Kalonji, 2021).…”
Section: Seedsmentioning
confidence: 99%
“…The most recent review centered around the extraction and analysis methods for phytochemicals of avocado seeds, including their chemical and functional properties. 11 Some review papers explore the health effect of the seed, including antioxidant, anti-inflammatory, antihypertensive, cytotoxic, and immunomodulatory activities of avocado seeds from Hass, Fuerte, or drymifolia varieties. [12][13][14] Additionally, Colombo and Papetti processed avocado seeds to produce biofuel and explored the seeds' adsorption capacity to remove contaminants from water.…”
Section: Introductionmentioning
confidence: 99%